Barriers to Peritoneal Dialysis in Aboriginal Patients. Issue 1 (3rd January 2018) - Mathew, Anna T.; Park, Joonho; Sachdeva, Mala; Sood, Manish M.; Yeates, Karen
Background: Aboriginal people in Canada have an unduly high burden of end-stage kidney disease (ESKD) and many live in rural settings. Peritoneal dialysis (PD) is a home-based dialysis modality that may provide a valuable alternative to in-center hemodialysis which is relatively underutilized by the Aboriginal population. Objective: We aim to assess the barriers to PD utilization in Aboriginal patients with ESKD. Design: This article is a prospective observational cohort study. Setting: The setting involves 3 predialysis clinics in Winnipeg, Kingston, and Moose Factory. Patients: The patients were 99 individuals (67 non-Aboriginal and 32 Aboriginal) who were at least 18 years of age with an estimated glomerular filtration rate of less than 30 mL/min/1.73m 2, and were enrolled in one of the 3 study sites from April 2011 to October 2013. Measurements: Patient demographics and comorbidities were documented. Barriers to PD, PD as modality choice, and Aboriginal status were assessed via patient survey upon study enrollment. PD use as the initial dialysis modality was assessed via monthly patient follow-up for 1 year after enrollment in the study. Methods: The patient survey was created based on literature review of known barriers to PD, repaired based on direct patient feedback, and tested for reliability via the test-retest method. Differences in PD choice, barriers to PD, and PD use between Aboriginal and non-Aboriginal patients were determined by chi-square test and logistic regression. Results: All patients enrolled in the study completed the survey. Mean age was 65.5 versus 54.6 years for non-Aboriginals and Aboriginals, respectively. Barriers to PD significantly associated with Aboriginal status were lack of money (odds ratio [OR]: 21.3; 95% confidence interval [CI]: 5.3-86.4; P < .0001) and anxiety (OR: 2.8; 95% CI: 1.1-7.1; P = .03). There was no difference in PD choice between non-Aboriginals and Aboriginals (66.7% vs 68.8%, respectively; P = .83). One of 67 non-Aboriginals (1.5%) and 5 of 32 Aboriginals (15.6%) died prior to initiating dialysis ( P = .013). No significant difference was observed between non-Aboriginals (33%) and Aboriginals (28%) in use of PD ( P = .81). Limitations: Small sample size was a limitation of this study. Conclusions: Aboriginal people in Canada have a disproportionately large burden of ESKD, and PD could provide an alternative to in-center hemodialysis for those living in rural areas. Our study identified anxiety and lack of money as barriers to PD significantly associated with Aboriginal status. When choosing dialysis modality, shared decision making between physicians and patient is of key importance to weigh all potential benefits and risks and emphasize the Aboriginal patient's values and preferences. These results can be used to guide future research and to help devise interventions targeting barriers to PD in Aboriginals.